Penerapan Kombinasi Metode ROC Dan MAUT Dalam Penentuan Calon Penerima Bantuan UKT Pada Universitas Budi Darma - Rajagukguk, Jumpa Dorisman; Mesran, M; Purba, Bister (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
During the 2019 Coronavirus Diseases pandemic, many people were affected socially and economically, especially parents of students. Therefore, the government through universities provides a solution to help the economy, one of which is through the Single Tuition Assistance (UKT) program. In making the decision to determine the prospective recipient of UKT Assistance, the university is still constrained by time because there is quite a lot of data that must be processed or selected manually and of course, must meet several criteria that have been set by the university. In order to assist universities in making decisions to determine prospective recipients of UKT Assistance, a decision support system is needed. The Rank Order Centroid (ROC) and MAUT (Multi-Attribute Utility Theory) methods are a combination of methods that support determining the priority criteria for prospective UKT Assistance recipients. In determining the candidates who are eligible to receive UKT Assistance according to the formula and method used, in order to obtain the highest value alternative that is entitled to receive the UKT Assistance. The results of the application of the combination of the two methods so as to obtain the highest 25 alternative values of the 30 alternatives as a calculation sample with the first rank alternative value of 0.707.